THE EFFECT OF GOVERNMENT INVESTMENT AND PRIVATE INVESTMENT ON POVERTY LEVEL IN SOUTH KALIMANTAN PROVINCE - M. Ramadhan (STTAL POSTGRADUATE - INTERNATIONAL CONFERENCE, 2021)
High-quality economic growth is economic growth that can encourage industrialization, can create the widest possible employment opportunities, and can improve people's incomes to reduce poverty levels. On the other hand, South Kalimantan Province is one of the regions in Indonesia that has a fairly large natural resource potential including the agricultural sector, plantation, and marine fisheries sub-sector, as well as the coal mining sector which attracts investment activities both from domestic sources in the form of Domestic Investment (PMDN) and Foreign Investment (PMA). Based on the KPPOD survey parameters, the investment climate condition of South Kalimantan Province is relatively conducive so that investment realization from year to year has increased. One of the goals to be achieved in developing investment, especially with the PMDN and PMA facilities, is to encourage the level of economic growth. Positive economic growth is needed because it means it has moved the wheels of the economy faster. Therefore, it is necessary to conduct research to test, prove and explain the Effect of Government Investment and Private Investment on Economic Growth, Employment Absorption, Income Inequality, and the Number of Poor Populations in Regencies/Cities in the South Kalimantan Province. Keywords: Investment, Poverty Level, South Kalimantan.